Elucidation of Structure–Activity Relations in Proton Electroreduction at Pd Surfaces: Theoretical and Experimental Study (Small 30/2022). Issue 30 (27th July 2022) - Schmidt, Thorsten O.; Ngoipala, Apinya; Arevalo, Ryan L.; Watzele, Sebastian A.; Lipin, Raju; Kluge, Regina M.; Hou, Shujin; Haid, Richard W.; Senyshyn, Anatoliy; Gubanova, Elena L.; Bandarenka, Aliaksandr S.; Vandichel, Matthias
Abstract : Proton Electroreduction In article number 2202410, Elena L. Gubanova, Aliaksandr S. Bandarenka, Matthias Vandichel, and co‐workers report the structure–activity relations that govern the complex electrochemical processes for the proton electro‐reduction on Pd(hkl) electrodes using a combination of theoretical and experimental approaches. The formation of subsurface hydride results in morphological changes, inducing a strain, which affects the activity toward this reaction.